Effect of Using Superplasticizer on Concrete Exposed to Sea Water: Pengaruh Penggunaan Supperplaticizer Pada Beton Terekspos Paparan Air Laut - Purwantoro, Didik Setyo; Muhammad Nur Fajar (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Development in coastal areas has a problem, namely concrete construction will come into direct contact with seawater. Seawater is one of the causes of failure in building structures. Innovations in the field of concrete material technology, one of which is to improve the properties of concrete, including the addition of certain materials, namely admixtures or additives to the concrete mixture, one of which is supperplaticizer. In this study, the compressive strength value of concrete immersed in 3 curing media will be compared, namely normal water, seawater in laboratory conditions and seawater directly. Based on the results of compressive strength, it shows that concrete that is directly exposed to seawater will experience a decrease in compressive strength. And after added the concrete supperplaticizer experiences an increase in the compressive strength value, this is in accordance with the supperplacizier properties which accelerate the hardening of the concrete and increase the sealability or density of the concrete. However, at compositions above 1% concrete, the compressive strength value has decreased.